Effectiveness of marketing communication program by Zoo Taiping and Night Safari / Siti Nuraznie Ibrahim - Ibrahim, Siti Nuraznie (2004)
Zoo Taiping and Night Safari (ZT&NS) are run by Taiping Municipal Council and located in Taiping Lake Gardens. It was established in 1961. It was the first zoo and the first zoo by night that is Night Safari in Malaysia. This study focused on the effectiveness of marketing communication program by ZT&NS. Like other non-profit organizations, ZT&NS want to achieve their mission and objective to be a main tourist attraction and as a place for recreation, education, conservation and research. So, the study on marketing issue relate with how many visitors have come to visit ZT&NS, besides trying to determine the level of awareness of visitors towards this zoo and how effective are the variables that chosen in order to test the hypothesis. The research design involves both exploratory and descriptive methods. The researcher explores all the necessary and relevant information through secondary data. Secondary data are made available via reference to books, journals, newspaper articles, ZT&NS publication and the internet. The descriptive study is applied to investigate the issue of the effective of marketing communication program by ZT&NS. From the research conducted, four key finding can be concluded, first, visitors f ZT&NS have good awareness on ZT&NS, second, most of the visitors are from local area. Thirdly, visitors mostly make a repeat visit and finally many visitors know about ZT&NS from their friends.